2010
DOI: 10.1002/jmri.22395
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging of the abdomen at 3.0 Tesla: Image quality and apparent diffusion coefficient reproducibility compared with 1.5 Tesla

Abstract: Purpose: To compare single-shot echo-planar imaging (SS EPI) diffusion-weighted MRI (DWI) of abdominal organs between 1.5 Tesla (T) and 3.0T in healthy volunteers in terms of image quality, apparent diffusion coefficient (ADC) values, and ADC reproducibility. Materials and Methods:Eight healthy volunteers were prospectively imaged in this HIPAA-compliant IRBapproved study. Each subject underwent two consecutive scans at both 1.5 and 3.0T, which included breathhold and free-breathing DWI using a wide range of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
164
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 46 publications
17
164
6
Order By: Relevance
“…This difficulty can be overcome using parallel imaging technology, as described in this study. Parallel imaging techniques help to reduce the echo train length and the echo spacing (6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…This difficulty can be overcome using parallel imaging technology, as described in this study. Parallel imaging techniques help to reduce the echo train length and the echo spacing (6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, other studies have reported no significant differences in ADCs of abdominal organs obtained using MRI at 3T vs. 1.5T. 31 Further studies will be necessary to fully evaluate the differences in ADC between 3T and 1.5T MRI.…”
Section: 19mentioning
confidence: 98%
“…So far, 1.5 T MR systems have mainly been applied for renal imaging. However, further investigations at higher field strength are necessary to improve SNR and contrast-to-noise ratio of these advanced MRI techniques by maintaining the specific absorption rate within uncritical values and high image quality [54].…”
Section: Resultsmentioning
confidence: 99%
“…Hueper et al [18] Yu et al [15] Inci et al [14] Chandarana et al [16] Zhang et al [13] Lu et al [20] Sigmund et al [11] Wittsack et al [12] Rosenkrantz et al [54] Hueper et al [21] ASL Artz et al [26] Pedrosa et al [28] Lanzman et al [29] Rossi et al [27] Cutajar et al [23] Wu et al [24] Boss et al [22] Schor-Bardach et al [30] BOLD Park et al [37] Xiao et al [36] Min et al [38] Yin et al [34] Michaely et al [43] Xin-Long et al [33] Park et al [37] Donati et al [42] Simon-Zoula et al [32] Zhang et al…”
Section: Animal Study Dwi/ Dtimentioning
confidence: 99%